The impact of the Community Based Public Works Programme of the Department of Public Works in Groutville - Mthembu, N. (Hymnal Nkosinathi) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPA)--University of Stellenbosch, 2003.